Clinical and microbiological effects of ozone nano-bubble water irrigation as an adjunct to mechanical subgingival debridement in periodontitis patients in a randomized controlled trial - Hayakumo, Sae; Arakawa, Shinichi; Mano, Yoshihiro; Izumi, Yuichi (Clinical oral investigations, 2013)
Aim Ozone nano-bubble water (NBW3) seems to be suitable as an adjunct to periodontal treatment owing to its potent antimicrobial effects, high level of safety, and long storage stability. The aim of the present study was to evaluate the clinical and microbiological effects of NBW3 irrigation as an adjunct to subgingival debridement for periodontal treatment. Methods Twenty-two subjects were randomly assigned to one of the two treatment groups: full-mouth mechanical debridement with tap water (WATER) or full-mouth mechanical debridement with NBW3 (NBW3). Clinical examination was performed at baseline and 4 and 8 weeks after treatment. Microbiological examination was carried out just before and after treatment and at 1 and 8 weeks posttreatment. Results There were significant improvements in all clinical parameters after 4 weeks in both groups. The reduction in the probing pocket depth and the clinical attachment gain after 4 and 8 weeks in the NBW3 group were significantly greater than those in the WATER group. Moreover, only the NBW3 group showed statistically significant reductions in the mean total number of bacteria in subgingival plaque over the study period. Conclusions The present study suggests that subgingival irrigation with NBW3 may be a valuable adjunct to periodontal treatment. Clinical relevance This study verified the potential of new antimicrobial agent, MNW3, as an adjunct to periodontal treatment.